Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1542/peds.110.3.553
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Oral Versus Normal and High-Dose Rectal Acetaminophen in the Treatment of Febrile Children

Abstract: There was no difference between the temperature decrement in patients treated with 15 mg/kg oral acetaminophen and the same or double dose rectally. Thus, there seems to be no evidence to support the use of higher doses of rectal acetaminophen for the treatment of fever in children. The rectal route proved to be as acceptable as the oral among parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 23 publications
1
27
1
1
Order By: Relevance
“…Although alternative dosing regimens have been suggested, [41][42][43] no consistent evidence has indicated that the use of an initial loading dose by either the oral (30 mg/kg per dose) or rectal (40 mg/kg per dose) route improves antipyretic efficacy. The higher rectal dose is often used in intraoperative conditions but cannot be recommended for use in routine clinical care.…”
Section: Acetaminophenmentioning
confidence: 99%
“…Although alternative dosing regimens have been suggested, [41][42][43] no consistent evidence has indicated that the use of an initial loading dose by either the oral (30 mg/kg per dose) or rectal (40 mg/kg per dose) route improves antipyretic efficacy. The higher rectal dose is often used in intraoperative conditions but cannot be recommended for use in routine clinical care.…”
Section: Acetaminophenmentioning
confidence: 99%
“…After proper lubrication, the nurse inserted the suppository beyond the internal sphincter. 23 For oral route, syrup containing 120 mg/5mL of acetaminophen was used. The dose was calculated in mg and was then converted to mL.…”
Section: Introductionmentioning
confidence: 99%
“…On average, about 50% of rectal acetaminophen will bypass the liver [8]. Because of reduced efficacy due to poor absorption and the risk of cumulative toxicity due to high or frequent doses, even American Academy of Paediatrics (AAP) has recommended that suppository be used only for oral intolerance cases like as vomiting [7][8][9]. In a meta-analysis, published by Goldstein et al [10] in 2008, it was found that there was no difference in oral and rectal acetaminophen antipyretic effects [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Leary et al on 38 children aged 2 to 54 months, it was found that oral acetaminophen (60 mg for children under one year of age and 120 mg for children older than one year) was more effective than rectal enema with a similar dose in controlling children's fever. They recommended that acetaminophen be administered orally to control fever in children [9][10][11]. Scolnik et al [9] showed no significant difference between the temperatures decrement (the maximum drop in temperature or final temperature or in temperature change during the 3 hours after administration) in children 6 months to 6 years of age treated with 15 mg/kg oral acetaminophen and the same or double dose rectally [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation